Identification of the Nicotianamine synthase (NAS) gene family in wheat (Triticum aestivum L.) and the role of its member TaNAS4-A in Zn and Fe transport - Gang Liu; Yixuan Sun; Pengyuan He; Yibo Wang; Yixuan Zhang; Qingfeng Li; Fenglou Liu; Shuangxi Zhang; Yingxia Zhang; Caixia Liu; Zhangjun Wang (Functional & Integrative Genomics, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Two-stage pattern of Dansgaard–Oeschger 19.2 during MIS 4: Evidence from a high-resolution stalagmite δ18O record in southwestern China and its global correlations - Zhenqiu Zhang; Yifei Wang; Fucai Duan; Jianshun Chen; Dianbing Liu; Qingfeng Shao; Yongjin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Compound climate hazards revealed by global modeling of drought, heatwaves, and land degradation - Jinping Liu; Yanqun Ren; Qingfeng Hu; Tie Liu; Xi Chen; Patrick Willems; Philippe De Maeyer (Global and Planetary Change, 2026)

Short-term nitric oxide gaseous treatment of post-rigor pork: Multidimensional impacts on meat quality, protein oxidation and proteolysis, and microstructure - Jiaye Zhu; Yongmao Ye; Liangyu Zhang; Haoyang Ma; Xinnuo Zhou; Yu Qi; Qingfeng Ge; Mangang Wu; Hai Yu; Rui Liu (Food Chemistry, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Biome-dependent forest GPP responses to compound drought and heat from 2001 to 2023 - Jinping Liu; Yanqun Ren; Qingfeng Hu; Shoukai Chen; Mingzhe Li (Agricultural and Forest Meteorology, 2026)

Coupling mechanism of iron oxidation-precipitation and optimized copper-zinc leaching in ultrasound-assisted oxygen pressure leaching of complex polymetallic chalcopyrite secondary concentrate - Qingfeng Liu; Yalong Liao; Jialei Li; Min Wu (Minerals Engineering, 2026)

Key exposure components and oxidative stress-driven health risks assessment of oil mist generated by metalworking fluids in industrial building environment - Yang Yang; Yilin Li; Yuming Zhang; Yi Wang; Yalin Liu; Ming Liu; Xudong Li; Yifan Qu; Mengdan Qiao; Qingfeng Cao (Journal of Hazardous Materials, 2026)

Plastic mulching and crop type govern the vertical distribution and composition of microplastics in a major agricultural irrigation system - Xuezheng Yu; Weiying Feng; Liu Wang; Yuxin Deng; Chia Min Ho; Yunping Han; Qingfeng Miao; Meng Zhao; José Manuel Gonçalves; Sundaravelpandian Kalaipandian (Environmental Research, 2026)

Design and single-site feasibility test of a trawl-resistant seafloor platform for broadband seismic observation in fishing-intensive shallow waters: a case study from the Bohai Sea - Xianfeng Li; Qingfeng Hua; Yanliang Pei; Chenguang Liu; Kaiben Yu; Yanpeng Zheng (Marine Geophysical Research, 2026)

SfIML-1 interacts with integrin β5 to mediate fungal conidial adhesion and immune activation in Spodoptera frugiperda - Fang-Fang Liu; Qi-Gui Gao; Yue Sun; Chao-Peng Liang; Hai-Yan Ren; Qingfeng Tang; Liang Wen; Bang-Xian Zhang; Xiang-Jun Rao (Pesticide Biochemistry and Physiology, 2026)

Mechanistic insights into chromium immobilization and uptake inhibition in lettuce mediated by endophyte-loaded biochar - Qizhen Liu; Jie Yuan; Ziyan Fan; Ancao Pan; Qingfeng Zhang; Rui Zhou; Nazish Jabeen Abbasi; Chao Yu; Ying Feng (Journal of Hazardous Materials, 2026)

Targeting the Wnt/β-catenin pathway: veratramine mitigates MNNG-induced gastric precancerous lesions - Pan Zhang; Xuelin Sun; Longteng Liu; Yatong Zhang; Jiaqi Bo; Wenli Huang; Yifan Na; Jingyi Zhang; Xiaoyun Qin; Qingfeng Luo (Molecular and Cellular Biochemistry, 2026)

AI-designed crop populations for sustainable intensification - Ning Luo; Junhan Wang; Morten Graversgaard; Renan C. Umburanas; De Li Liu; Qirui Li; Jonathan Storkey; Simon Willcock; Pu Wang; Qingfeng Meng (Trends in Plant Science, 2026)

Valorization of allelochemical-rich olive pomace: Comprehensive effect microbial nutrient release and ursolic acid-enhanced uptake improve crop growth and quality - Xisi Sun; Shuyang Wang; Fangzhu Guo; Junkai Wang; Guoqing Xiao; Qingfeng Wu; Yuhong Liu (Journal of Cleaner Production, 2026)

Inferring irrigation regimes and sunshine duration from the distribution and spectral characteristics of farmland microplastics - Hangzheng Zhao; Xu Han; Changming Cao; Ziyi Zan; Bo-Tao Zhang; Jiamin Wang; Qingfeng Tang; Weifeng Yue; Yan Liu (Environmental Pollution, 2026)

Seismic behaviours of T-shaped steel-concrete-steel sandwich composite walls under different axial compression ratios - Qingfeng Liu; Tao Wang; Jia-Bao Yan (Engineering Structures, 2026)

Defect-mediated rigid-flexible coupled architecture for upcycling of spent O3-type sodium-ion cathodes - Qingfeng Liu; Jinhua Shi; Fanbin Hu; Zitong Fei; Yun Shen; Haigang Dong; Qi Meng; Peng Dong; Yingjie Zhang (Chemical Engineering Journal, 2026)

In situ gas-foaming strategy to construct nitrogen-doped porous hollow carbon spheres for ultra-broadband microwave absorbers - Youjun Jiang; De-Zhuang Wang; Mengqian Zhang; Yuerong Li; Yazhong Chen; Jun Yang; Xianlong Zhang; Qingfeng Liu; Xueping Wu (Chemical Engineering Journal, 2026)

Synergistic mitigation of apple replant disease: Biochar and compound bacterial fertilizer restructure soil microbial communities and promote plant growth - Yawen Gao; Yunheng Jiang; Houshan Wang; Qingfeng Chang; Bingyu Zhang; Mei Wang; Yusong Liu; Li Xiang; Chengmiao Yin; Zhiquan Mao (Applied Soil Ecology, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Study on the effects of ultraviolet inactivation in the process of gynogenetic development of grass carp eggs induced by mirror carp sperm - Wangchao He; Yu Sun; Kuo Chen; Junwen Liang; Binchao Liang; Xinyan Zhu; Qingfeng Liu; Yang Chen; Jialin Tang; Fuzhong Yang; Chun Zhang; Bo Chen; et al. (Aquaculture, 2026)

Seep-related carbonates on continental shelves: Distinctive processes and morphologies revealed by the Qiongdongnan Shelf, South China Sea - Hongli Wang; Qiang Zhao; Fangqi Wang; Qingfeng Hua; Qiuhong Xie; Yangting Liu; Chenguang Liu; Yanliang Pei; Xishuang Li; Yikai Feng; Fei Cao (Marine Geology, 2026)

Effect of critical atomizing-flow distributor on thermal–hydraulic performance of finned evaporator - Zhili Sun; Jinjin Wang; Qifan Wang; Guanyuan Su; Qingfeng Bie; Yue Zhao; Jinfeng Chen; Hongyu Zhao; Zhan Wang; Xiaoyu Liu; Yihan Liu; Wenfu Zhang; et al. (International Journal of Refrigeration, 2026)

Improvement of probiotic tolerance to hyperosmotic environments by whey protein-citrus pectin conjugate: effect on the physicochemical, structural, survival of probiotic microencapsulation - Xuan Lu; Ning Zhang; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

Flow pattern regime of ventilated cavity around an axisymmetric body under a varying incoming flow velocity: an experimental study - Zichao Shao; Liang Hao; Yue Wu; Taotao Liu; Qingfeng Yang; Dongning Fan; Biao Huang (Ocean Engineering, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

High-performance, durable bamboo conductive macrofibers based triboelectric nanogenerator for stable harvesting water wave energy - Jiaqi Liao; Qingyu Meng; Wenwen Zhu; Wenhao Xu; Yang Peng; Shitao Shi; Zewei Ye; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Prediction of in situ seafloor sediment sound speed with machine learning - Mujun Chen; Linqing Zhang; Xinfeng Hu; Xiangmei Meng; Guangming Kan; Siyou Tong; Jingqiang Wang; Guanbao Li; Baohua Liu; Qingfeng Hua; Siqi Wu; Xiaobo Zhang (Journal of Oceanology and Limnology, 2026)

Anammox enhanced anoxic/oxic/oxic/anoxic process for treating extremely low carbon/nitrogen ratio wastewater: Performance and mechanism at different hydraulic retention times - Qingfeng Cheng; Cheng Wang; Lichao Nengzi; Chao Liu; Erdeng Du; Mingguo Peng (Journal of Water Process Engineering, 2026)

Separation and enrichment of platinum from spent petroleum reforming catalysts via carrier-directed dissolution under alkaline conditions - Qingfeng Xiong; Han Yang; Lang Liu; Jibiao Han; Yu Shen; Wenhui Ma; Yakun Zhang; Ruiling Yuan; Chao Wang (Journal of Environmental Chemical Engineering, 2026)

Facet-dependent metal-support interactions of Ru/CeO2 dictate the activity for direct deoxygenation of m-cresol - Yuxin Shang; Wenhui Yue; Zihao Liu; Ruoyu Zhang; Qingfeng Ge; Xinli Zhu (Fuel, 2026)

Enrichment mechanism and clean utilization of sodium-iron in high alkali and high iron coal in Beishan coal Mine, Xinjiang - Jiaxin Li; Hongyang Bai; Wenfeng Wang; Hengyan Liu; Kexin Che; Peng Wang; Qingfeng Lu (Fuel, 2026)

Multi-head attention driven aggregation-differentiation network for probabilistic groundwater depth forecasting and depth-stratified early warning: A multi-site efficient framework - Jing Xu; Siyuan Liu; Jinran Wu; Yuming Mo; Kun Wang; Qingfeng Ji; You-Gan Wang; Ling Li (Environmental Modelling & Software, 2026)

Multi-objective optimization of oxygen transfer and hydrodynamic shear in dual-impeller stirred tanks via integrated computational fluid dynamics and machine learning framework - Qingfeng Gu; Shuoyan Ji; Yongqiang Liu; Yongbo Wang; Junxiong Yu; Zejian Wang; Yingping Zhuang; Chao Li (Bioresource Technology, 2026)

Gaussian Function Affine Transformation Model: A Bridge Between Laboratory and Downhole Logging NMR in Shale Oil Reservoirs - Junjie Wang; Pengfei Zhang; Weizheng Gao; Wenbiao Li; Nengwu Zhou; Guohui Chen; Qingfeng Li; Chao Liu; Shuangfang Lu (Natural Resources Research, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Research on vertical ecological compensation mechanism based on ecosystem services supply-demand balance—A case study of the Nine Plateau Lakes in Yunnan Province - Jianjun Sheng; Qingfeng Xiao; Zhanpeng Du; Qin Zhang; Yan liu; Yinglan Xue (Environment, Development and Sustainability, 2026)

Childhood susceptibility to PFAS-associated endocrine disruption: NHANES age-stratified analysis and PFOS mouse model validation - Qiming Yang; Wenxin Bai; Yujun Liu; Xiuxian Huang; Bing Zou; Zubair Muhammad; Uswa Farooq; Qingfeng Zhai; Nan Liu (Reproductive Toxicology, 2026)

Effects of anthropogenic activities on soil microbial communities and greenhouse gas fluxes in coastal wetlands of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Zihao Wang; Kun Li; Chenmiao Liu; Chen Li; Zhengxi Cai; Xinkun Zhao; Xinyi Xu; Hongjie Di; Qingfeng Chen (Journal of Environmental Sciences, 2026)

Stabilization mechanisms, cell density, and survival of probiotic encapsulation prepared with thiolated hyaluronic acid-whey protein complex: For potential colon targeting probiotic delivery system - Ning Zhang; Xuan Lu; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

Progestins as emerging contaminants in soil: An investigation on their pollution characteristics and ecological risks - Qianwen Jiao; Zhenzhen Xu; Yuzhen Liu; Yimin Li; Yifan Zhao; Qingfeng Chen; Xiaoyan Shen (Environmental Research, 2026)

Multi-trait analysis to identify key factors influencing wheat lodging resistance and validation of an integrative lodging index - Hao Ren; Qingfeng Dong; Siting Li; Dezheng Liu; Xubin Zhang; Xue Wang; Liang Chen; Yin-Gang Hu (European Journal of Agronomy, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Swell correction for sub-bottom profile data using variational mode decomposition - Yibao Xiao; Xishuang Li; Kai Liu; Qingfeng Hua; Lejun Liu; Chenguang Liu (Marine Geophysical Research, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Impedance inversion of high-frequency Chirp sub-bottom profiles constrained by borehole data - Linqing Zhang; Xishuang Li; Lejun Liu; Xiangmei Meng; Qingjie Zhou; Kai Liu; Qingfeng Hua; Jingqiang Wang (Marine Georesources & Geotechnology, 2026)

Experimental and numerical study on ice-induced vibration control of jacket-type offshore wind turbine using tuned mass damper - Rui Wang; Jigang Zhang; Zhehao Ma; Qingfeng Yan; Feifei Liu; Zaixian Chen; Wei Li; Yun Niu (Ocean Engineering, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

Influence of target spectrum selection in wind spectrum fitting on fatigue damage assessment accuracy for wind turbine blades - Jiantao Liu; Yibing Liu; Chao Zhou; Qingfeng Gao; Haolin Yin (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Seismic behaviour of H-shaped steel-concrete-steel composite walls with innovative C-channel connectors to enhance resilience - Jin Wang; Yan Lu; Qingfeng Liu (Engineering Structures, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Cost-minimizing alternative dosage regimens of imipenem/cilastatin/relebactam for patients with renal impairment: a pharmacokinetic/pharmacodynamic simulation study - Xiaoping Shi; Donghui Lao; Qing Xu; Xiaoyu Li; Bijue Liu; Qingfeng He; Xiao Zhu; Qianzhou Lv (European Journal of Clinical Pharmacology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Bacterial communities of rhizolith- and root-associated in the Tengeri Desert, China - Jian Chen; Qingfeng Sun; Ruirui Chen; Zhihao Zhang; Zhen Liu; Gongyou Chen (Rhizosphere, 2025)

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

Effect of coating pretreatment on sensory quality of vacuum low temperature fried crisp jujube - Ruizhu Wang; Mingqiang Xu; Qingfeng Han; Yunpeng Liu; Kai Chen (International Journal of Gastronomy and Food Science, 2025)

Efficient removal of Pb2+ by iron-doped hydroxyapatite: Synthesis, adsorption, kinetics and mechanisms - Yan Li; Yuxia Zhong; Hang Lei; Qingfeng He; Fengchu Liao; Sisi Tang; Mengdi Liu; Yue-Fei Zhang (Environmental Research, 2025)

Genome-wide identification of zinc finger-homeodomain (ZF-HD) gene family and expression analysis during abiotic stress in rye - Qingfeng Li; Yuzhao Ren; Jiaohui Long; Zhaoyi Wang; Feifei Dou; Shilei Wang; Chunying Liu; Xiaodong Wang; Caixia Liu; Fenglou Liu; Zhangjun Wang (Genetic Resources and Crop Evolution, 2025)

Hydrodynamics knowledge-driven path planning for safety-constrained energy-saving in amphibious unmanned ground vehicles - Jun Luo; Jing Huang; Huayan Pu; Fanglong Wang; Qingfeng Li; Gang Wang; Mingyang Liu (Ocean Engineering, 2025)

CoCA: Spatial cooperative simulation and future prediction of “land-population-economy” in urban agglomerations - Chenglong Zeng; Yao Yao; Jiayao Liu; Zhenhui Sun; Kun Zhou; Dongsheng Chen; Qingfeng Guan (Landscape and Urban Planning, 2025)

Multifunctional hydrogel-modified laminated wood for high-strength and fire-resistant structural applications - Zewei Ye; Haomeng Yu; Wenwen Zhu; Shitao Shi; Jiaqi Liao; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2025)

Mechanistic insights into metformin's anti-hyperuricemic effect: Targeting PPP/DNPB/XOD-mediated purine pathway, purinosome assembly, and gut microbiota homostasis in rats - Qiuxia Yu; Huijun Liao; Wenwen Tan; Lieqiang Xu; Guoshu Lin; Zhixuan Ai; Qingfeng Xie; Yuhong Liu; Yucui Li; Xiaobo Yang; Ziren Su; Guo Ma; et al. (Chemico-Biological Interactions, 2025)

Integrated Analysis of Phenotypic and Hepatic Transcriptomic Profiles Reveals Enhanced Cold Tolerance in Triploid Crucian Carp - Suifei Tao; Zexun Zhou; Shandong Chen; Jialin Cui; Yude Wang; Kaikun Luo; Wei Liu; Qingfeng Liu; Wuhui Li; Shaojun Liu (Fishes, 2025)
Cold stress poses a critical threat to fish survival by triggering metabolic dysfunction, oxidative damage, immune suppression, and apoptosis. However, hybrid polyploid fish triploid crucian carp (3nRCR, 3n = 150) demonstrate superior stress tolerance. In this study, we investigated the cold adaptation mechanisms in different ploidy cyprinid fishes: triploid crucian carp compared to its diploid improved red crucian carp (Carassius auratus red var., RCC, 2n = 100, ♀) and improved allotetraploid (4nAT, 4n = 200, ♂) progenitors. Under controlled cooling, 3nRCR lost equilibrium at a significantly lower temperature (3.2 °C) than RCC (4.0 °C) and 4nAT (4.5 °C), confirming its superior enhanced cold resistance. Histological examination revealed minimal tissue damage in 3nRCR, characterized by reduced gill inflammation and cellular apoptosis. Transcriptomics revealed triploid-specific molecular strategies: 3nRCR uniquely activated retinol metabolism and metabolic rewiring (arginine/proline metabolism, oxidative phosphorylation). Notably, in the immune-related NLR signaling pathway, both nlrp1 and nlrp3 (key inflammasome components) were significantly downregulated in 3nRCR (p

Impact of calcium alginate gel-urea modified dry water on free radical spectral signatures and suppression mechanisms in methane explosions - Bin Peng; Qiuhong Wang; Jun Deng; Chi-Min Shu; Guoqiang Dong; Qingfeng Wang; Chao Ma; Rui Guo; Jianxiong Liu (Process Safety and Environmental Protection, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Occurrence, distribution, and potential risk of 61 glucocorticoids in soils in Shandong Province, China - Qianwen Jiao; Yifan Zhao; Yimin Li; Yuzhen Liu; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2025)

Electrospinning-mist polymerized antibacterial and super-hydrophilic nanofiber membrane for efficient dust filtration and enhanced comfort in mines - Gang Zhou; Liwei Jiang; Bo Wei; Pengjin Liu; Jiafa Du; Tingting Fan; Song Xin; Rulin Liu; Qingfeng Xu; Seeram Ramakrishna (Chemical Engineering Journal, 2025)

Deciphering the regulatory network of carbon isotope discrimination in bread wheat through genome-wide association studies and genomic prediction - Qingfeng Dong; Shan Lu; Hao Ren; Dezheng Liu; Shen-ao Gao; Xuefen Cai; Shanshan Zhang; Muhammad Ateeq; Liang Chen; Yin-gang Hu (Theoretical and Applied Genetics, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

Statistical investigation of marine bacterial extracellular polysaccharides: deciphering the interplay among environmental adaptation, species distribution, and biomedical potential - Yuanyuan Jiang; Shuo Liang; Qingfeng Niu; Chanjuan Liu; Guangli Yu; Guoyun Li (Marine Life Science & Technology, 2025)

Decrypting gene-spliced like and fast kinetic energy storage modes of Na/Mg dual doped manganese oxides cathode for high-performance aqueous zinc-ion batteries - Xiaosha Cui; Yaxiong Zhang; Qingfeng Wu; Sida Deng; Shengyuan Wang; Jiuzhou Wang; Yupeng Liu; Junli Zhang; Erqing Xie; Jiecai Fu (Chemical Engineering Journal, 2025)

Mechanisms of plant-derived and microbial residue carbon in coastal wetland soils in response to salinity gradients - Xinkun Zhao; Jingyu Sun; Chenmiao Liu; Enyue Zhang; Guoliang Zhao; Qingfeng Chen (CATENA, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

A coordinate control strategy for load following operation of sodium-cooled fast reactor system - Qingfeng Jiang; Jinrong Jin; Areai Nuerlan; Yizhe Liu; Jiashuang Wan; Pengfei Wang (Annals of Nuclear Energy, 2025)

Using total Kalman filter to extract time-varying signals in PWV time series - Dantong Zhu; Kefei Zhang; Peng Sun; Suqin Wu; Qingfeng Hu; Peipei He; Weibo Yin; Yafei Wang; Junguo Liu (Advances in Space Research, 2025)

Ecosystem Shifts and Cladocera Responses in a Freshwater Lake in Semi‐Arid Regions: The Successional Synergistic Effects of Natural and Human Factors in the Past 170 Years - Longjuan Cheng; Bin Xue; Jinliang Liu; Xiangzhen Kong; Can Zhang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Wenxiu Zheng (Journal of Biogeography, 2025)
Aim Freshwater lake ecosystems in semi‐arid regions are highly fragile and complex. However, the driving forces behind changes in temperate lake ecosystems at a regional scale in China remain largely unclear, primarily due to the lack of multidecadal to centennial regional studies. This study focuses on Hulun Lake, the largest freshwater lake in northern China's semi‐arid region, with the aim of elucidating the characteristics and driving mechanisms of freshwater lake ecosystems in such areas. Location Hulun Lake, the largest freshwater lake in northern China's semi‐arid region (48.55° ~ 49.33° N, 116.97° ~ 117.81° E). Time Period From the 1840s to 2010s AD. Major Taxa Studies Zooplankton Cladocera. Methods High‐resolution multiproxy palaeoecological data (including biological and geochemical indices), human activities parameters and observational datasets from the lake basin are used to explore ecosystem shifts and Cladocera responses in Hulun Lake, located in a semi‐arid region, over the past 170 years. The hypothesis that changes in the zooplankton Cladocera community composition within the ecosystem are driven by synergistic interactions among multiple factors was tested using effective approaches based on generalised additive models (GAM) and redundancy analysis (RDA). Results The results indicate that both internal factors (such as lake sedimentary environment, fish catches, lake water level, organic matter and nutrients) within the lake and external factors (including population, urbanisation rate and livestock husbandry) in the surrounding basin have been key drivers influencing the structure of Cladocera in Hulun Lake over the past 170 years. The originally predominant littoral Cladocera species ( Chydorus sphaericus . sl.) were replaced by planktonic (Bosminidae) since the 1980s accompanied by a decline in diversity, which corresponds with the process of eutrophication and pollution in the lake. Main Conclusions The dynamics of the Cladocera assemblages indicate that the lake ecosystem is vulnerable to further imbalance since the 2000s due to the ongoing synergistic effects of declining fishery catches, increasing livestock numbers, rising populations, urbanisation rates and declining water levels in semi‐arid regions.

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Correction: Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

A new type of triploid fish derived from female Carassius auratus red var. × male Gobiocypris rarus - Fanglei Liu; Ziyi Huang; Xuanyi Zhang; Bei Li; Lujiao Duan; Jianming Yu; Qizhi Liu; Siyang Huang; Hongwen Liu; Qiuli Liang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Stretchable, controlled release of active substances, and biodegradable chitosan-polyvinyl alcohol hydrogel film for antibacterial and chilled meat preservation - Debao Wang; Chaoqiao Zhu; Qingfeng Yang; Yuqian Xu; Dequan Zhang; Daoying Wang; Fang Liu; Chengli Hou (Food Chemistry, 2025)

Gels stability by improving the hydrophobic region of casein: Effect of the mogrosides on the structure, microstructure, and antioxidant activities in vitro digestive of the casein acid-induced gel - Yingdi Wang; Kun Sun; Yutong Hu; Yujie Lin; Jiaxuan Li; Qingfeng Ban; Fei Liu (Food Hydrocolloids, 2025)

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

Effects of anthropogenic activities on soil microbial community structure and methane anaerobic oxidation rate in coastal wetlands of Yellow River Delta, China - Chenmiao Liu; Zihao Wang; Xia Gao; Kun Li; Lei Yu; Jingyu Sun; Hongjie Di; Xiaoya Xu; Qingfeng Chen (Applied Soil Ecology, 2025)

Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Enhancement of the flavor compound 3-Methylbutanal and sensory quality in sausages fermented by Lactococcus lactis CGMCC 31087: Leucine and α-Ketoglutaric acid as supplements - Lei Chen; Congjiao Wei; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Food Chemistry, 2025)

Root Transcriptome of Wheat Genotypes Under Zinc Sufficient and Deficiency Conditions - Gang Liu; Ming Ma; Zhangjun Wang; Qingfeng Li; Fenglou Liu; Yixuan Sun; Shiping Hu; Caixia Liu (Journal of Plant Growth Regulation, 2025)

The formation and growth characteristics of an all-female hybrid crucian carp - Lujiao Duan; ChaoLiang Shen; Jingjing Lin; Xiaoxia Xiong; Huan Sun; Ziyi Huang; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Identifying low-to-middle-income residents’ secondary activity patterns using smart card data - Ziyan Zhao; Meihan Jin; Mei-Po Kawn; Qingfeng Zhou; Yongxi Gong; Yu Liu (Travel Behaviour and Society, 2025)

Explosion suppressing effects of Mg(OH)2/NH4H2PO4 compound powders on the methane explosion and its microscopic mechanism about capturing intermediate products - Qiuhong Wang; Leilei Zhu; Jun Deng; Qingfeng Wang; Jing Han; Dong Zhao; Youjie Sheng; Ting Pan; Jianxiong Liu (Fuel, 2025)

Green development strategy for efficient quercetin- loaded whey protein complex: Focus on quercetin loading characteristics, component interactions, stability, antioxidant, and in vitro digestive properties - Qingguan Liu; Puying Liu; Qingfeng Ban (Food Chemistry, 2025)

Deciphering the regulatory network of lignocellulose biosynthesis in bread wheat through genome-wide association studies - Qingfeng Dong; Hao Ren; Xuefen Cai; Yujie Zhang; Shan Lu; Dezheng Liu; Muhammad Ateeq; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

Improvement of quercetin bioaccessibility by whey protein isolate/D-tagatose conjugates: Effect on the structural characterization through simultaneous rheological and FTIR techniques - Feifei Chen; Yao Meng; Yujie Lin; Qingfeng Ban; Fei Liu (Food Hydrocolloids, 2025)

Experimental Study on the Differences in Acoustic Emission Precursor Between Rockburst and Brittle Failure Based on the Data Mining Method - Jie Sun; Dongqiao Liu; Manchao He; Qingfeng Sun; Huili Huang (Rock Mechanics and Rock Engineering, 2025)

Screening of priority antibiotics in Fenhe River Basin based on the environmental exposure, ecological effects, and human health risk - Ruimin Liu; Qingfeng Long; Yue Liu; Linfang Wang (Chemosphere, 2025)

Multi-omics reveals the molecular mechanisms of rapid growth in distant hybrid fish - Xuanyi Zhang; Fanglei Liu; Bei Li; Lujiao Duan; Jianming Yu; Ziyi Huang; SiYang Huang; Hongwen Liu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Effect of Borehole Pressure Relief on Rockburst: Insights from Borehole Cooperative Deformation Mechanism - Dongqiao Liu; Ziqian Zhang; Jinsong Yang; Qingfeng Sun; Zhengxi Liu; Jie Sun (Rock Mechanics and Rock Engineering, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Water and land use in China's food systems: Exploring potential mitigation strategies - Wenjun Shi; Hanlin Liu; Yosef Steinberger; Yuanchao Hu; Yang Yang; Qingfeng Meng; Guanghui Xie (Sustainable Production and Consumption, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

Mining genomic regions associated with stomatal traits and their candidate genes in bread wheat through genome-wide association study (GWAS) - Dezheng Liu; Shan Lu; Renmei Tian; Xubin Zhang; Qingfeng Dong; Hao Ren; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

The soil microclimate and microbial characteristics jointly drive the response of vegetation productivity to changes in snow cover — A global meta-analysis - Qingfeng Xu; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xinhao Li (Science of The Total Environment, 2024)

Experimental investigation on the ventilated cavitating flow characteristics around an axisymmetric body with an unsteady ventilation - Liang Hao; Housheng Zhang; Qingfeng Yang; Taotao Liu; Biao Huang; Guoyu Wang (Ocean Engineering, 2024)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Anti-enterovirus 71 activity of native fucosylated chondroitin sulfates and their derivatives - Qingfeng Niu; Han Zhou; Xiaoyao Ma; Yuanyuan Jiang; Chanjuan Liu; Wei Wang; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2024)

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Spatial-temporal characteristics of port infrastructures on sulfur-oxide concentrations of coastal port in China - Lang Xu; Jiyuan Wu; Qingfeng Zhao; Jihong Chen; Jutong Liu; Fangren Gao; Xiaorui Liu; Jianghao Xu (Ocean & Coastal Management, 2024)

Innovation of the global international ship registry system: Evolution process and future reforms - Jihong Chen; Jianghao Xu; Qingfeng Zhao; Zeng Yuan; Li Li; Huangziyi Chen; Yinuo Liu; Yuan Xiang (Ocean & Coastal Management, 2024)

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Benzo(a)pyrene exposure impacts cerebrovascular development in zebrafish embryos and the antagonistic effect of berberine - Ke Xu; Qian Wang; Ying Zhang; Yuehong Huang; Qingfeng Liu; Meng Chen; Chonggang Wang (Science of The Total Environment, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Biosynthesis pathway of flavor compound 3-methylbutanal derived from leucine by Lactococcus lactis 517: From a transcriptomics perspective - Lei Chen; Rui Liu; Chenxiang He; Mangang Wu; Qingfeng Ge; Hai Yu (Food Bioscience, 2024)

Microtopographic response of tilled loess slopes during stages of water erosion development - Wenli Rao; Qingfeng Zhang; Zhenyu Qian; Jincheng Liu; Guoqing Zhao (CATENA, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Effects of ambient temperature and humidity on COPD mortality in Ganzhou city, China - Chenyang Shi; Jinyun Zhu; Qingfeng Wu; Yanhong Liu; Yanbin Hao (International Journal of Biometeorology, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Heterogeneous feature learning network for multimodal remote sensing image collaborative classification - Xuchu Yu; Zhixiang Xue; Guopeng Yang; Anzhu Yu; Bing Liu; Qingfeng Hu (International Journal of Remote Sensing, 2024)

Late Middle Pleistocene micromammals of the Bianfudong paleolithic site, Heqing, western Yunnan - Meijing Chang; Qijun Ruan; Qingfeng Shao; Jianhui Liu; Qiang Li; Xijun Ni (Quaternary International, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Inoculation fermentation with Lactobacillus fermentum L28 and Staphylococcus epidermidis S24 for improving the protein degradation of air-dried goose - Mangang Wu; Chen Gu; Likun Duan; Peipei Yin; Tianhao Zhu; Yuyu Xu; Qing Yin; Rui Liu; Qingfeng Ge; Hai Yu (Food Chemistry, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Ferroptosis is involved in trophoblast cells cytotoxicity induced by black phosphorus nanoparticles - Ruolan You; Yaming Mu; Jiaqi Zhou; Chunying Wang; Zhenya Fang; Yu Liu; Shiyu Liu; Qingfeng Zhai; Changqing Zhang (Toxicology, 2024)

U-series in situ dating of secondary carbonates associated with rock paintings using LA-MC-ICPMS - Yanuo Jiao; Yue Liu; Zeji Lu; Rainer Grün; Qingfeng Shao (Quaternary Geochronology, 2024)

High strength and water tolerance fish gelatin-xanthan gum acid-induced electrostatic film by melt extrusion method - Xiaohan Chen; Zhuolin Liu; Wenya Ma; Hao Wang; Qingfeng Dong; Li Li (Food Hydrocolloids, 2024)

A biomass-enhanced bentonite slurry for shield tunnelling in the highly permeable soil - Tao Xu; Xiaoyu Wu; Jiaxin Liu; Qingfeng Shi; Jinquan Shi (Tunnelling and Underground Space Technology, 2024)

Electrochemical characterizations and galvanic effect of chalcopyrite leaching and passivation-A review - Xin-Jie Liu; Yalong Liao; Haifei Ma; Qingfeng Liu (Minerals Engineering, 2024)

Investigation on enhanced oil recovery and CO2 storage efficiency of temperature-resistant CO2 foam flooding - Xin Chen; Qingfeng Zhang; Japan Trivedi; Yiqiang Li; Jianbin Liu; Zheyu Liu; Shun Liu (Fuel, 2024)

A repertoire of single nucleotide polymorphisms (SNPs) of major fecundity BMPR1B gene among 75 sheep breeds worldwide - Chunna Cao; Qian Zhou; Yuxin Kang; Zhanerke Akhatayeva; Peiyao Liu; Yuheng Bai; Ran Li; Yu Jiang; Qingfeng Zhang; Xianyong Lan; Chuanying Pan (Theriogenology, 2024)

Forces driving ecological degradation in southern China during the MIS3: Natural or anthropogenic? - Qiong Chen; Xiaobo Huang; Hua Tu; Qingfeng Shao; Xiaoming Sun; Qiaofen Liu; Wei Wang; Zhongping Lai; Xiaoqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

In-situ emulsification in low-tension surfactant/polymer systems: Impacts on enhanced oil recovery - Zheyu Liu; Yiqiang Li; Seyed Hossein Hejazi; Xiaoyan Wang; Xin Chen; Huoxin Luan; Qingfeng Hou; Li Liu (Fuel, 2024)

Benthic foraminiferal assemblages in the coastal zone of the yellow river delta: Environmental significance and characteristics of microbial diversity - Shuyang Huang; Qing Li; Xiaohua Qiu; Hong You; Ruimin Lv; Wei Liu; Qingfeng Chen; Tiantian Wang; Jing Zhang; Junjian Ma; Zihao Wang; Shigang Ding (Continental Shelf Research, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Seafloor Sediment Acoustic Properties on the Continental Slope in the Northwestern South China Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Qingfeng Hua; Guangming Kan; Chenguang Liu (Journal of Marine Science and Engineering, 2024)
The acoustic properties of seafloor sediments on continental slopes play a crucial role in underwater acoustic propagation, communication, and detection. To investigate the acoustic characteristics and spatial distribution patterns of sediments on the continental slope, a geoacoustic experiment was conducted in the northwestern South China Sea. The experiment covered two sections: one crossing the shelf and slope in the downslope direction, and the other near the shelf break in the along-slope direction. In situ techniques, sediment sampling, and laboratory measurements were used to acquire data on sediment acoustic properties (such as sound speed and attenuation) and physical properties (including particle composition, density, porosity, and mean grain size). The experimental findings revealed several key points: (1) Acoustic properties of shallow water coarse-grained sediments and deep-sea sediments were higher when measured in the laboratory compared to in situ measurements. (2) Relationships between measured attenuation and physical properties, as well as between sound speed and mean grain size, showed deviations from previous empirical equations. (3) Sediment acoustic and physical properties exhibited significant variations in the downslope direction, while showing gradual variations in the along-slope direction. These variations can be attributed to sedimentary environmental factors such as material sources, hydrodynamic conditions, and water depth.

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

A review on aroma-active compounds derived from branched-chain amino acid in fermented meat products: Flavor contribution, formation pathways, and enhancement strategies - Lei Chen; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Trends in Food Science & Technology, 2024)

Design and optimization of liquid nitrogen precooling BOG re-liquefaction process for LNG ships - Lesheng Liu; Ting Guo; Xianglei Kong; Jiubing Shen; Qingfeng Jiang; Yanyan Zhou; Xing Tong (International Journal of Refrigeration, 2024)

LncFASA promotes cancer ferroptosis via modulating PRDX1 phase separation - Xiao Fan; Fangzhou Liu; Xiang Wang; Ying Wang; Yu Chen; Chengyu Shi; Xinwan Su; Manman Tan; Qingfeng Yan; Jinrong Peng; Jianzhong Shao; Yan Xiong; et al. (Science China Life Sciences, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Enhanced Asian hydroclimate instability during early MIS 6.5 - Dianbing Liu; Yongjin Wang; Xinggong Kong; Qingfeng Shao; Yi Li (Quaternary Science Reviews, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

Potential of novel zinc-based nanomaterials on the microbial community, antibiotic resistance genes, and DNA replication in animal manure - Haibo Zhang; Lizhi Li; Gangfu Chen; Nancheng Yin; Jiangao Guo; Xinrui Ni; Yixin Liu; Ke Wu; Weikun Guan; Cheng Zhang; Xiaochun Wu; Shi Wenkai; et al. (Chemical Engineering Journal, 2024)

Prediction Model of the Sound Speed of Seafloor Sediments on the Continental Shelf of the East China Sea Based on Empirical Equations - Guangming Kan; Junjie Lu; Xiangmei Meng; Jingqiang Wang; Linqing Zhang; Guanbao Li; Baohua Liu; Qingfeng Hua; Mujun Chen (Journal of Marine Science and Engineering, 2023)
Based on the data of the acoustic and physical properties of seafloor sediments obtained on the continental shelf area of the East China Sea (ECS), prediction equations of the sediment sound speed based on single and dual parameters were established, and the correlation of the sound speed with physical parameters was discussed. The results show that the sediment sound speed (c) is strongly correlated with water content (w), density (ρ), void ratio (e), mean grain size (Mz) and median grain size (Md), and the coefficient of determination R2 of the empirical regression equation is generally greater than 0.80, while the empirical regression equation coefficient of determination R2 of the compression coefficient (a) and compression modulus (E) are slightly lower, with 0.79 and 0.73, respectively. The coefficients of determination of the dual parameter regression equations between sediment sound speed with physical property parameters are generally higher than those of the single parameter equations, which are all higher than 0.90 indicating better prediction performance. The sensitivity of the physical parameters to the sound speed was analyzed, and the result shows that the sequence of sensitivity from high to low influence on sediment sound speed is void ratio, density, compressibility coefficient, median grain size and mean grain size. The prediction equations established in this study are a good extension and supplement to marine geoacoustic models and is of great significance for obtaining the acoustic properties of the seafloor sediments on the shelf of the East China Sea.

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

Biotechnology Remediation and Environmental Behavior of Microplastics in Soils: A Review - Weiying Feng; Yuxin Deng; Yingnan Cao; Jing Liu; Yunping Han; Jianguo Liu; Qingfeng Miao; Fang Yang; Ying Zhu; John P. Giesy (Reviews of Environmental Contamination and Toxicology, 2023)

Stalagmite-based long-term and multi-centennial hydroclimatic variations in southwestern China during the Holocene and relations to global climate change - Fucai Duan; Zhenqiu Zhang; Dianbing Liu; Jianshun Chen; Qingfeng Shao; Yongjin Wang (Quaternary Science Reviews, 2023)

Mechanism and evolution trend of digital green fusion in China's regional advanced manufacturing industry - Qingfeng Tian; Weikang Shen; Yueqi Wang; Lijun Liu (Journal of Cleaner Production, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Improvement of non-fat yogurt gel syneresis by heat-unfolded whey protein isolate/mogrosides complexes: Effect on the structural characterization through simultaneous rheological and FTIR techniques - Qingfeng Ban; Zonghao Liu; Xuan Zhang; Bo Song; Yunqing Jiang; Jianjun Cheng (Food Hydrocolloids, 2023)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

Enhanced VOCs adsorption and oxidation by hydrophobic-layer-modified YMn2O5 mullite catalyst with ultralow single-atom Pt loading - Jiaqin He; Yaru Wang; Xunxun Li; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Advances in Ag2S-based thermoelectrics for wearable electronics: Progress and perspective - Min Zhu; Xiao-Lei Shi; Hao Wu; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Fabrication of Supramolecular System Derived from Poly β-cyclodextrin Coupling Quinoline Dderivative and Its Fluorescence Sensing of Zinc Ion in Pure Water Environment - Wenping Zhu; Yinlong Chen; Zengchen Liu; Weijie Yang; Yanxia Li; Yahong Chen; Qingfeng Li; Yali Cui; Baodui Wang (Journal of Fluorescence, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Boosting hydrogen evolution on MoS2 via synergistic regulation of interlayer dislocations and interlayer spacing - Longlu Wang; Feiran Zhang; Ning Sun; Lingbin Xie; Ting Zhi; Qingfeng Zhang; Zhongzhong Luo; Xia Liu; Shujuan Liu; Qiang Zhao (Chemical Engineering Journal, 2023)

Advances in Ag2S-based thermoelectrics for wearable electronics: progress and perspective - Min Zhu; Xiao-Lei Shi; Hao Wu; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Comparison of spatiotemporal burial and contamination of heavy metals in core sediments of two plateau lakes with contrasting environments: implication for anthropogenic-driven processes - Xiaolei Wang; Qingfeng Jiang; Zihan Zhao; Ximou Han; Jinliang Liu; Qun Liu; Bin Xue; Hao Yang (Environmental Monitoring and Assessment, 2023)

Interannual variation in gross ecosystem production and evapotranspiration in a temperate semiarid grassland undergoing vegetation recovery - Xinhao Li; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xin Jia; Yun Tian; Chuan Jin; Xiaoshuai Wei; Xinyue Liu; Hongxian Zhao; Qingfeng Xu; Shaorong Hao (Agricultural and Forest Meteorology, 2023)

Optimization and control strategy of BOG re-liquefaction process for LNG vessels - Ting Guo; Lesheng Liu; Jiubing Shen; Qingfeng Jiang; Sichen Wu; Yanyan Zhou; Yi Liu (International Journal of Refrigeration, 2023)

Discovery of acylated isoquercitrin derivatives as potent anti-neuroinflammatory agents in vitro and in vivo - Jie Liu; Ailing Hui; Jinghe Wang; Qingfeng Hu; Shengnan Li; Yuanli Chen; Zeyu Wu; Wencheng Zhang (Chemico-Biological Interactions, 2023)

Pyrite and sulfur-coupled autotrophic denitrification system for efficient nitrate and phosphate removal - Xuzhen Liu; Changsheng Zhao; Tongtong Xu; Wei Liu; Qingfeng Chen; Luzhen Li; Yu Tan; Xiaokai Wang; Yanan Dong (Bioresource Technology, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Low-dose graphene oxide promotes tumor cells proliferation by activating PI3K-AKT-mTOR signaling via cellular membrane protein integrin αV - Zhiwen Zheng; Abuduliaizezi Halifu; Juan Ma; Leyi Liu; Qingfeng Fu; Bocun Yi; E. Du; Dawei Tian; Yong Xu; Zhihong Zhang; Jianqiang Zhu (Environmental Pollution, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Effects of load-related parameters on the dynamic response of concrete-filled double-skin steel tube K-joints under lateral impact loading - Qingfeng Yan; Jigang Zhang; Zhehao Ma; Feifei Liu; Guoliang Zhao; Chi Gu; Hanyu Song; Weicheng Zhang (Ocean Engineering, 2023)

Flexible and mechanically strong MXene/cellulose-lamellae sheets for electromagnetic interference shielding - Yushan Yang; Kaicong Chen; Baokang Dang; Chao Wang; Yipeng Chen; Ming Liu; Yingying Li; Xiaochun Zhang; Qingfeng Sun (Chemical Engineering Journal, 2023)

Design, synthesis, antibacterial activity, and mechanism of novel resveratrol derivatives containing an 1,3,4-oxadiazole moiety - Ju Peng; Yong Zhang; Xing Liu; Yue Zou; Hongyi Song; Sheng Wang; Qingfeng Cai; Jixiang Chen; Deyu Hu (Pesticide Biochemistry and Physiology, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Metabolism of hydrogen peroxide by Lactobacillus plantarum NJAU-01: A proteomics study - Lei Chen; Rui Liu; Suyun Li; Mangang Wu; Hai Yu; Qingfeng Ge (Food Microbiology, 2023)

PneuNet: deep learning for COVID-19 pneumonia diagnosis on chest X-ray image analysis using Vision Transformer - Tianmu Wang; Zhenguo Nie; Ruijing Wang; Qingfeng Xu; Hongshi Huang; Handing Xu; Fugui Xie; Xin-Jun Liu (Medical & Biological Engineering & Computing, 2023)

Responses of Soil Humus Composition and Humic Acid Structural Characteristics to the Addition of Different Types of Biochar in Phaeozems - Qi Wang; Yingxue Zhu; Lianzhou Xu; Baiyang Chen; Chunzhu Liu; Xianfa Ma; Qingfeng Meng; Bing Liu; Zongwei Huang; Yusheng Jiao; Ye Yuan (Journal of Soil Science and Plant Nutrition, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Characteristics and health risk assessment of heavy metal pollution in atmospheric particulate matter in different regions of the Yellow River Delta in China - Ting Liu; Changsheng Zhao; Qingfeng Chen; Luzhen Li; Guorui Si; Lei Li; Beibei Guo (Environmental Geochemistry and Health, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Advanced nitrogen removal performance and microbial community structure of a lab-scale denitrifying filter with in-situ formation of biogenic manganese oxides - Qingfeng Cheng; Zongyang Liu; Yang Huang; Shanshan Feng; Erdeng Du; Mingguo Peng; Jie Zhang (Journal of Environmental Management, 2023)

Loofah sac-like three-dimensional interwoven network composed of Van-PEG-MWCNTs for rapid and efficient capture of Staphylococcus aureus - Yu Chen; Yong Liu; Qingfeng Dong; Min Fan; Li Li (Food Bioscience, 2023)

How to effectively prevent alienation behavior of prefabricated construction developers: an optimization analysis of regulatory strategies - Xijie Ai; Qingfeng Meng; Zhen Li; Wenyao Liu (Environmental Science and Pollution Research, 2023)

Heat-induced changes in epitopes and IgE binding capacity of soybean protein isolate - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Protein modification, IgE binding capacity, and functional properties of soybean protein upon conjugation with polyphenols - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Pathway and driving forces to complete forest transition in inner Mongolia of China - Xiaoyu Wu; Guiyan Liu; Qingfeng Bao (Environmental Development, 2023)

Experimental and numerical study on the dynamic behavior of concrete-filled double steel tubular T-joint under impact loading - Qingfeng Yan; Jigang Zhang; Feifei Liu; Zhehao Ma; Guoliang Zhao; Chi Gu; Hanyu Song; Yang Zhao (Ocean Engineering, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Ni-Mn spinel aerogel catalysts with adsorption induced superior activity for Low-Temperature toluene oxidation - Jiaqin He; Xunxun Li; Yaru Wang; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Jinghui He; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Simultaneous promotion of mechanical and electrical properties of hot-pressing halloysite-based mullite ceramics through carbon incorporation - He Zhang; Liangcao Yin; Qingfeng Liu; Yazhong Chen; Shi Jin; Kesong Xiao; Huanyu Zhu; Xianlong Zhang; Xueping Wu (Applied Clay Science, 2023)

Discovery of quinazoline compound as a novel nematicidal scaffold - Yu Wang; Hongyi Song; Sheng Wang; Qingfeng Cai; Yong Zhang; Yue Zou; Xing Liu; Jixiang Chen (Pesticide Biochemistry and Physiology, 2023)

Low quantity of Pt loaded onto CeCoOx nanoboxes: Surface–rich reactive oxygen species for catalytic oxidation of toluene - Yunchong Liu; Xunxun Li; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Mechanochemical incorporation of magnesium in iron-based composite surface for efficient hydrogenation of carbon dioxide to light olefin - Haipeng Chen; Ningning Ma; Chenwei Wang; Chenlei Liu; Xiaoyu Zhang; Weiwei Yuan; Wenqiang Li; Shixue Zhou; Qingfeng Yang; Xun Feng (Fuel, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

2.5 V “water in salt” aqueous micro-supercapacitors based on polypyrrole-coated NiCo layered double hydroxides - Xijuan Li; Xukun Wang; Guo Liu; Xinyi Sui; Qingfeng Wu; Xinge Wang; Xueliang Lv; Erqing Xie; Zhengxing Zhang (Chemical Engineering Journal, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Sediment Waves on the Western Slope of the Chukchi Rise (Arctic Ocean) and Their Implications for the Paleoenvironment - Qingfeng Hua; Guanbao Li; Qingjie Zhou; Shujiang Li; Tengfei Xu; Baohua Liu; Hongxia Chen (Journal of Marine Science and Engineering, 2022)
Based on multibeam bathymetric data and high-resolution shallow sub-bottom profiles acquired during China’s 10th Arctic Scientific Expedition Cruise in 2019, a sediment wave field was found on the western slope of the Chukchi Rise, in the Arctic Ocean. This sediment wave field developed on the lower slope with water depths of between 1200 m and 1800 m and stretched 15 km in the downslope direction. It comprised several parallel sediment waves, with wavelengths ranging from 700 m to 3400 m and wave heights from 12 m to 70 m. In the vertical direction, well-stratified deposits, tens of meters thick, were affected by sediment waves, which exhibit asymmetric waveforms and upslope migration trends. The morphological and seismostratigraphic characteristics of the sediment waves suggested their genesis as a result of the interaction between the bottom current and seafloor morphology, which was also supported by hydrographical data adjacent to the sediment wave field. It was infered that this bottom current was related to the Arctic Circumpolar Boundary Current, which many researchers suggest flows through the study area.

High-Frequency Dependence of Acoustic Properties of Three Typical Sediments in the South China Sea - Jingqiang Wang; Zhengyu Hou; Guanbao Li; Guangming Kan; Baohua Liu; Xiangmei Meng; Qingfeng Hua; Lei Sun (Journal of Marine Science and Engineering, 2022)
The acoustic characteristics of three fine-grained sediments (silty sand, silt, silty clay) in the South China Sea (SCS) were measured and analyzed at high frequency range of 27–247 kHz. The measurement results show that the sound speed dispersion is a positive linear relation at the measured frequency range, and the attenuation follows nonlinear frequency dependence, α = kfn, where n ranges from 0.59 to 0.85 for the three different sediments in the SCS. The frequency dependence of sound speed and attenuation were compared with the published literature. It was found that for silty clay, clayey silt, silt, and silty sand, the dispersion characteristics of these four sediments are basically consistent; in general, the dispersion of coarse particles is significant, and that of fine particles is weak, and permeability is the key parameter that determines the inflection point of high frequency to low frequency. By modeling these sediments with the Biot–Stoll model, it was found that the Biot–Stoll model can better predict the frequency-dependent characteristics of sound attenuation in a high-frequency band under the matching constraints of sound speed dispersion characteristics, indicating that the Biot–Stoll model has good applicability to different types of sediments in a high-frequency band.

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Development of suspension culture technology and hormone effects on anthocyanin biosynthesis for red Cyclocarya paliurus cells - Yuan Liu; Qi Liang; Daobang Tang; Yuqin Chen; Jianwei Zang; Wenjia Zhao; Jiguang Chen; Qingfeng Zhang; Zhongping Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Can digital finance promote corporate green innovation? - Jiamin Liu; Yalin Jiang; Shengdao Gan; Ling He; Qingfeng Zhang (Environmental Science and Pollution Research, 2022)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Dynamic reward and penalty strategies of green building construction incentive: an evolutionary game theory-based analysis - Qingfeng Meng; Yingying Liu; Zhen Li; Changzhi Wu (Environmental Science and Pollution Research, 2021)

Soil and ambient air mercury as an indicator of coal-fired power plant emissions: a case study in North China - Zhonggen Li; Xufeng Chen; Wenli Liu; Taishan Li; Guangle Qiu; Haiyu Yan; Mingmeng Wang; Ji Chen; Guangyi Sun; Qingfeng Wang; Xinbin Feng (Environmental Science and Pollution Research, 2021)

Relationships between the sound speed ratio and physical properties of surface sediments in the South Yellow Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Baohua Liu; Guangming Kan; Guozhong Han; Qingfeng Hua; Yanliang Pei; Lei Sun (Acta Oceanologica Sinica, 2021)

Alpha 1-antichymotrypsin may be a biomarker for the progression of amnestic mild cognitive impairment - Shunjie Liu; Junhao Pan; Ke Tang; Qingfeng Lei; Lu He; Xiaodong Cai; Zhong Li (Acta Neurologica Belgica, 2021)

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

Study on dynamic damage characteristics of coal under alternating hydraulic pressure - Qingfeng Xu; Yanbin Yu; Rulin Liu; Weimin Cheng; Haotian Yang (Bulletin of Engineering Geology and the Environment, 2021)

Susceptibility assessment of soil erosion in overlaying diluvial fan of shallow underground pipelines - Qingdong Wang; Yingbin Zhang; Qingfeng Lv; Chenlin Xiang; Xiao Xia; Jing Liu (Bulletin of Engineering Geology and the Environment, 2021)
Soil erosion is a serious hazards occurring in overlaying diluvial fans of shallow underground pipelines. To learn the extent of soil erosion in such landforms, we propose a method of susceptibility assessment of soil erosion based on a case study of the Chaka diluvial fan, Qinghai Province, China. First, we conducted a field investigation at 24 sites, to obtain the land surface properties. Then, vital information such as soil anti-scouribility, permeability, density, sectional water volume, and pipeline burial depth was collected. The slope grade and the vegetation index were determined with the geographic information system (GIS) technology. Further, the analytic hierarchy process (AHP) was used to determine the weight of various indices on the potential susceptibility of shallow underground pipelines. The susceptibility classification of the study area soil erosion was obtained based on the GIS overlay analysis tool. Lastly, the susceptibility classification was compared with the results of the field investigation. Their consistency indicates that the proposed method can be successfully implemented to accurately assess soil erosion. The erosion mechanism indicates that occlusion and cementation have an important influence on the susceptibility intensity in overlaying diluvial fans of shallow underground pipelines.

Tectonic implications of the subduction of the Kyushu-Palau Ridge beneath the Kyushu, southwest Japan - Chenglong Xia; Yanpeng Zheng; Baohua Liu; Qingfeng Hua; Long Ma; Xianfeng Li; Qiuhong Xie (Acta Oceanologica Sinica, 2021)

Characterization, identification and evaluation of a novel wheat-Agropyron cristatum (L.) Gaertn. disomic addition line II-30-5 - Qingfeng Li; Yuqing Lu; Cuili Pan; Zhangjun Wang; Fenglou Liu; Jinpeng Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2020)

Correction to: MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

Seafloor elastic-parameter estimation based on a regularized AVO inversion method - Yangting Liu; Yu Zhong; Kai Liu; Qingfeng Hua (Marine Geophysical Research, 2020)

Mechanism study of trans-lamina cribrosa pressure difference correlated to optic neuropathy in individuals with glaucoma - Qingfeng Liang; Leying Wang; Xuyang Liu (Science China Life Sciences, 2020)

Assessing impacts of climate change on habitat suitability of Coregonus ussuriensis and other coldwater fishes in northern China - Baoxiu Xing; He Chen; Qingfeng Chen; Yan Zhang; Zifang Liu; Zhao Yang (Environmental Science and Pollution Research, 2019)

Runoff and sediment variation and attribution over 60 years in typical Loess Plateau basins - Qiaoqiao Zhao; Li Wang; Hao Liu; Qingfeng Zhang (Journal of Soils and Sediments, 2019)

Additional application of aluminum sulfate with different fertilizers ameliorates saline-sodic soil of Songnen Plain in Northeast China - Meng Zhou; Xiaobing Liu; Qingfeng Meng; Xiannan Zeng; Jizhou Zhang; Dawei Li; Jie Wang; Weiling Du; Xianfa Ma (Journal of Soils and Sediments, 2019)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

Performance and microbial community profiles in pilot-scale biofilter for ammonia, iron and manganese removal at different dissolved oxygen concentrations - Qingfeng Cheng; Yang Huang; Lichao Nengzi; Jianying Liu; Jie Zhang (World Journal of Microbiology and Biotechnology, 2019)

Oxymatrine improves L-arginine-induced acute pancreatitis related intestinal injury via regulating AKT/NFkB and claudins signaling - Hui Zang; Zhiqiang Zhang; Qingfeng Liu; Huimin Xiao; Tian Sun; Enling Guo; Lankun Zhang; Bensong Gong (Medicinal Chemistry Research, 2019)

Comparative Analysis of Fractional Vegetation Cover Estimation Based on Multi-sensor Data in a Semi-arid Sandy Area - Qiuyu Liu; Tinglong Zhang; Yizhe Li; Ying Li; Chongfeng Bu; Qingfeng Zhang (Chinese Geographical Science, 2019)

Sound speed dispersion characteristics of three types of shallow sediments in the southern yellow sea - Guangming Kan; Baohua Liu; Jingqiang Wang; Xiangmei Meng; Guanbao Li; Qingfeng Hua; Lei Sun (Marine Georesources & Geotechnology, 2018)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Experimental study of the ballast in situ sediment acoustic measurement system in South China Sea - Jingqiang Wang; Guanbao Li; Baohua Liu; Guangming Kan; Zhiwen Sun; Xiangmei Meng; Qingfeng Hua (Marine Georesources & Geotechnology, 2018)

An aeromagnetic survey system based on an unmanned autonomous helicopter: Development, experiment, and analysis - Yanliang Pei; Baohua Liu; Qingfeng Hua; Chenguang Liu; Yuqiang Ji (International Journal of Remote Sensing, 2017)

Effect of mevalonic acid on cholesterol synthesis in bovine intramuscular and subcutaneous adipocytes - Xiaomu Liu; Wei You; Haijian Cheng; Qingfeng Zhang; Enliang Song; Fachun Wan; Hong Han; Guifen Liu (Journal of Applied Genetics, 2016)

Intranasal H102 Peptide-Loaded Liposomes for Brain Delivery to Treat Alzheimer’s Disease - Xiaoyao Zheng; Xiayan Shao; Chi Zhang; Yuanzhen Tan; Qingfeng Liu; Xu Wan; Qizhi Zhang; Shumei Xu; Xinguo Jiang (Pharmaceutical Research, 2015)

Antigen-conjugated N-trimethylaminoethylmethacrylate Chitosan Nanoparticles Induce Strong Immune Responses After Nasal Administration - Qingfeng Liu; Xiaoyao Zheng; Chi Zhang; Xiayan Shao; Xi Zhang; Qizhi Zhang; Xinguo Jiang (Pharmaceutical Research, 2015)

Chloroplast DNA-based genetic diversity and phylogeography of Pyrus betulaefolia (Rosaceae) in Northern China - Yu Zong; Ping Sun; Jing Liu; Xiaoyan Yue; Qingfeng Niu; Yuanwen Teng (Tree Genetics & Genomes, 2014)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Spectroscopic, Viscositic and Molecular Modeling Studies on the Interaction of 3′-Azido-Daunorubicin Thiosemicarbazone with DNA - Fengling Cui; Qingfeng Liu; Hongxia Luo; Guisheng Zhang (Journal of Fluorescence, 2014)

A genome-wide identification and characterization of mircoRNAs and their targets in ‘Suli’ pear (Pyrus pyrifolia white pear group) - Qingfeng Niu; Minjie Qian; Guoqin Liu; Fengxia Yang; Yuanwen Teng (Planta, 2013)

Comparison of the Therapeutic Effectiveness of Sustained Low-Efficiency Dialysis (SLED) with Continuous Blood Purification (CBP) in Critically Ill Patients - Junzhang Cheng; Shouliang Hu; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2013)

Cooperation among Numb, MDM2 and p53 in the development and progression of pancreatic cancer - Weiwei Sheng; Ming Dong; Jianping Zhou; Xin Li; Qingfeng Liu; Qi Dong; Feng Li (Cell and Tissue Research, 2013)

Complete genome sequence of Escherichia coli O157:H7 lytic phage JL1 - FengGuang Pan; Han Wu; JinHua Liu; YongXing Ai; XianMei Meng; RiZeng Meng; Qingfeng Meng (Archives of Virology, 2013)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

Soil quality in east coastal region of China as related to different land use types - Qingfeng Meng; Jingsong Yang; Rongjiang Yao; Guangming Liu (Journal of Soils and Sediments, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Roles of intracellular fibroblast growth factors in neural development and functions - Xu Zhang; Lan Bao; Liu Yang; QingFeng Wu; Shuai Li (Science China Life Sciences, 2012)

Overexpressed mutant optineurin(E50K) induces retinal ganglion cells apoptosis via the mitochondrial pathway - Qingfeng Meng; Jia Lv; Hongyan Ge; Lu Zhang; Fei Xue; Yuanmao Zhu; Ping Liu (Molecular Biology Reports, 2012)

Nose-to-Brain Transport Pathways of Wheat Germ Agglutinin Conjugated PEG-PLA Nanoparticles - Qingfeng Liu; Yehong Shen; Jie Chen; Xiaoling Gao; Chengcheng Feng; Lu Wang; Qizhi Zhang; Xinguo Jiang (Pharmaceutical Research, 2012)

Hepatic stellate cells produce vascular endothelial growth factor via phospho-p44/42 mitogen–activated protein kinase/cyclooxygenase-2 pathway - Yi Zhao; Yanqing Wang; Qiang Wang; Zhengrong Liu; Qingfeng Liu; Xin Deng (Molecular and Cellular Biochemistry, 2012)

Spectroscopic and Molecular Modeling Studies of the Interaction Between 4′-O-(α-L-Oleandrosyl)daunorubicin and Human Serum Albumin and Its Analytical Application - Ruina Huo; Cui Li; Fengling Cui; Guisheng Zhang; Qingfeng Liu; Xiaojun Yao (Journal of Fluorescence, 2012)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

The activation of extracellular signal-regulated kinase is responsible for podocyte injury - Shufang Liu; Jie Ding; Qingfeng Fan; Han Zhang (Molecular Biology Reports, 2010)